2017
DOI: 10.1021/acsearthspacechem.6b00006
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Isotopic Fractionation in Ammonia during Adsorption on Silicate Surfaces

Abstract: Adsorption is a fundamental phenomenon that occurs at various interfaces; however, the isotopic fractionation in stable isotopes associated with this process has not yet been well documented for most molecules. In this study, we conducted ammonia adsorption experiments on two silicate minerals, montmorillonite and saponite, to determine the nitrogen isotopic fractionation during the process. Ammonia adsorbed on these minerals is up to +44‰ enriched in 15 N relative to initial ammonia. The degree of 15 N enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…If NH 3 dry deposition is influenced by N isotopic equilibrium reactions between NH 3 and the surface deposited NH + 4 , this would have resulted in NH 3 depleted in 15 N as it is removed from the atmosphere, resulting in lower δ 15 N(NH 3 ) values . Indeed, a previous NH 3 absorption-desorption study on minerals has shown the preferential removal of 15 NH 3 from the gaseous phase, with the degree of 15 N depletion of the gaseous NH 3 dependent upon the adsorbed NH 3 amount (Sugahara et al, 2017). Thus, as the traffic plume ages in the absence of fresh emissions, we would expect NH 3 dry deposition influences and the potential for N isotopic exchange reactions between the air and tunnel surface to be most significant, which might explain the lower δ 15 N(NH x ) values observed during periods when the tunnel was closed.…”
Section: Traffic-plume δ 15 N(nh 3 ) Variabilitymentioning
confidence: 97%
“…If NH 3 dry deposition is influenced by N isotopic equilibrium reactions between NH 3 and the surface deposited NH + 4 , this would have resulted in NH 3 depleted in 15 N as it is removed from the atmosphere, resulting in lower δ 15 N(NH 3 ) values . Indeed, a previous NH 3 absorption-desorption study on minerals has shown the preferential removal of 15 NH 3 from the gaseous phase, with the degree of 15 N depletion of the gaseous NH 3 dependent upon the adsorbed NH 3 amount (Sugahara et al, 2017). Thus, as the traffic plume ages in the absence of fresh emissions, we would expect NH 3 dry deposition influences and the potential for N isotopic exchange reactions between the air and tunnel surface to be most significant, which might explain the lower δ 15 N(NH x ) values observed during periods when the tunnel was closed.…”
Section: Traffic-plume δ 15 N(nh 3 ) Variabilitymentioning
confidence: 97%
“…The adsorption of ammonium either by montmorillonite or by zeolite Na–P was controlled mostly by the ion-exchange processes, as summarized in eqs –. Other studies demonstrated the controlling of the ammonium adsorption by (A) the successful replacement of the zeolitic interchannel water and the montmorillonite interlayer water by the dissolved ammonium ions creating coordination complexes with the existing replaceable ions, (B) the occurrence of physical trapping for the ammonium ions within the interchannel of the zeolite structure or between the montmorillonite units, and (C) the normal electrostatic attraction processes , (Figure ). …”
Section: Resultsmentioning
confidence: 99%
“…The source of NH 4 + is unclear, but a possibility is that adsorbed NH 4 + was released from clays during HE crushing. NH 4 + is readily adsorbed onto silicate mineral surfaces 37 , and the relatively high concentrations of other base cations likely results in desorption via cation exchange. Dissolved silicon (DSi; as dissolved silicic acid), and Fe 2+ were also released during both HE and LE crushing, with lower concentrations in the LE crushed samples.…”
Section: Discussionmentioning
confidence: 99%